Nifuratel Induces Triple-Negative Breast Cancer Cell G2/M Phase Block and Apoptosis by Regulating GADD45A - Yuhang Hou; Hongyun Hao; Yan Yuan; Jing Zhang; Zhengrui Liu; Yimin Nie; Shichang Zhang; Shengtao Yuan; Mei Yang (MDPI AG, 2024)
(1) Background: Nifuratel (NF113), derived from nitrofuran, has a specific anti-tumor effect. However, the potential mechanisms of NF113 in triple-negative breast cancer remain unknown. (2) Methods: In the study, CCK8 assay and colony formation assays were used to evaluate the inhibition effect of NF113 on cell proliferation. Apoptosis and cell cycle distribution were tested by flow cytometry. The mechanism of NF113's anti-tumor effect was predicted by transcriptome sequencing and verified by using PCR and Western blot experiments. Breast cancer organoids constructed from the patient-derived tumor xenograft model and the MDA-MB-468 xenograft mouse model were established to evaluate the effect of NF113. (3) Results: Our study showed that NF113 had an anti-tumor effect on triple-negative breast cancer both in vitro and in vivo. NF113 also induced apoptosis and G2/M phase arrest in triple-negative breast cancer cells. Our experimental data further verified that NF113 reduced GADD5A mRNA and protein expression, which were significantly upregulated in breast cancer, with downstream CDC25C and AKT phosphorylation changes. (4) Conclusions: Our data provided compelling evidence that NF113 inhibited breast cancer growth via upregulating GADD45A. Conclusion: NF113 was able to exert inhibitory effects on the proliferation of triple-negative breast cancer in vivo and in vitro, which may induce G2/M phase arrest via the GADD45A/CyclinB/CDK1 pathway and apoptosis via GADD45A/JNK/P38.